Feasibility Study of Fiber to the Home Networks for Optical Fiber Loss and Attenuation - Budiman, Edy; ., Haviluddin; Wati, Masna; Taruk, Medi; Jati Setyadi, Hario; Santoso Pakpahan, Herman (International Journal of Engineering and Technology, 2018)
The utilization of optical fiber cable as a data transmission medium has provided various benefits and advantages in terms of data transfer and economically because it can reduce the use of many copper cables. The purpose of this study was to evaluate the feasibility of Fiber To The Home (FFTH) networks by measuring and analyzing power losses caused by attenuation along the fiber optic cable. Measuring tools for attenuation use JDSU MTS-8000 while the power measurement uses Optical Power Meter. Feasibility specifications refer to ITU-T G.984. recommendations. The analysis results show that of the 110 customers observed, the average value of Link Power Budget is 20.58 dB, with an average power margin of 5.57dBm. If comparing the results of the ITU-T G.984 recommendation, it stated that was accepted, still in accordance with the rules specifications. Feasibility studies of FTTH networks on the issue of power loss and attenuation are needed in an effort to maintain the quality of service to customers. It also has a relationship with planning and developing system installations in the future.Â